2012
DOI: 10.1108/17410401211205632
|View full text |Cite
|
Sign up to set email alerts
|

Current state of public sector performance management in seven selected countries

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 23 publications
5
69
0
4
Order By: Relevance
“…Currently, one of the indicators of government performance accountability measurement is LAKIP (Permendagri number 34 of 2011). LAKIP was originally created as an annual performance report that requires government agencies to provide an overview of mission, vision, strategic objectives, and key performance indicators and provide mechanisms for linking key performance indicators to goals and organization budgets (Rhodes et al, 2012). However, LAKIP is currently one of the assessment criteria of successful local government performance by the central government.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, one of the indicators of government performance accountability measurement is LAKIP (Permendagri number 34 of 2011). LAKIP was originally created as an annual performance report that requires government agencies to provide an overview of mission, vision, strategic objectives, and key performance indicators and provide mechanisms for linking key performance indicators to goals and organization budgets (Rhodes et al, 2012). However, LAKIP is currently one of the assessment criteria of successful local government performance by the central government.…”
Section: Introductionmentioning
confidence: 99%
“…If the ruling party is not the one that they vote, civil servants incline to spend most of the time in the office condemning ruling government and having debate with those who favour the ruling government. This phenomenon is not healthy and if not controlled could lead to lower productivity (Rhodes et al, 2013).…”
Section: Attitude Towards Governmentmentioning
confidence: 99%
“…Yao, Kam and Chan (2007) supported this by saying that senior management in the public administration sector should be made more aware of what knowledge management can do to help improve organizational efficiency and effectiveness. Rhodes, Biondi, Gomes, Melo, Ohemeng, Perez-Lopez, Rossi and Sutiyono (2013), when comparing the performance of public sector in Brazil, Italy, Portugal, Spain, Ghana, Indonesia and Ireland, found that administrative culture and the attitudes of elites are critical determinants of public sector performance.…”
Section: Journal Of Public Administration and Governancementioning
confidence: 99%
“…In contrast, public administrations are still facing big challenges concerning the implementation and use of IT PM concepts [4][5][6][7][8]. How IT PM can be implemented and used in public administrations is still an under-researched field [9].…”
Section: Introductionmentioning
confidence: 99%